From trickster to badman : the Black folk hero in slavery and freedom - Roberts, John W. (John Willie), 1949- (University of Pennsylvania Press, 1989)
To protect their identity and values, Africans enslaved in America transformed various familiar character types to create folk heroes who offered models of behavior both recognizable to them as African people and adaptable to their situation in America. Roberts specifically examines the Afro-American trickster and the trickster tale tradition, the conjurer as folk hero, the biblical heroic tradition, and the badman as outlaw hero. -- Publisher description from http://www.upenn.edu (Oct. 11, 2011).